A predictive method for the shear strength—displacement behavior of rockfill materials - Tennison Freire de Souza Junior; Sidnei Helder Cardoso Teixeira; Alessander Kormann (REM: International Engineering Journal, 2025)
Abstract Rockfill material is widely used in the construction of rockfill dam bodies, protective slope linings, and drainage systems, as well as in the stabilization of natural slopes. This material possesses high mechanical strength, excellent durability against erosive processes, and is economically viable for geotechnical solutions. Estimating resistance and elastoplastic parameters often relies on literature data, since full-scale tests are challenging and costly. This article investigates the shear stress (τ) versus relative displacement (δ) behavior and the friction angle of failure (ϕ) in large-scale shear tests on rockfill samples with varying mean diameters (D50). It also simulates τ versus δ behavior using the mathematical models of Clough and Duncan (1971) and Teixeira (2003) for comparison. The analyses showed that the hyperbolic model by Clough and Duncan (1971) and Teixeira (2003), when properly calibrated, can accurately simulate the mechanical behavior of the rockfill.